Optical measurements of KOH, KCl and K for quantitative K-Cl chemistry in thermochemical conversion processes. (1st July 2020) - Weng, Wubin; Zhang, Yuhe; Wu, Hao; Glarborg, Peter; Li, Zhongshan
Abstract: Potassium and chlorine chemistry at high temperature is of great importance in biomass utilization through thermal conversion. In well-defined hot environments, we performed quantitative measurements of main potassium species, i.e., potassium hydroxide (KOH), potassium chloride (KCl) and K atoms, and the important radical OH. The concentrations of KOH, KCl and OH radicals were measured through a newly developed UV absorption spectroscopy technique. Quantitative measurements of potassium atoms were performed using tunable diode laser absorption spectroscopy at the wavelength of 404.4 and 769.9 nm to cover a wide concentration dynamic range. The reaction environment was provided by a laminar flame burner, covering a temperature range of 1120–1950 K and global fuel-oxygen equivalence ratios from 0.67 to 1.32. Potassium and chlorine were introduced into the combustion atmosphere by atomized K2 CO3 or KCl water solution fog. The experimental results were compared to modeling predictions to evaluate a detailed K-Cl mechanism. For most cases, the experimental and simulation results were in reasonable agreement. However, the over-prediction of K atom concentration at low temperature fuel-rich condition and the overall under-prediction of KCl concentration call for further investigation. It was demonstrated that the optical methods and the well-defined hot environments could provide quantitative investigations widely applicable to different homogeneous reactions in thermochemical conversion processes, and in evaluation of corresponding reaction mechanisms with reliable data.